Evaluating Biochar Impact on Topramezone Adsorption Behavior on Soil under No-Tillage and Rotary Tillage Treatments: Isotherms and Kinetics - Uwamungu, Jean Yves (Int J Environ Res Public Health, 2019)
The evaluation of biochar application on the adsorption behavior of topramezone on soil under no-tillage (NT) and rotary tillage treatments (RT) has been assessed. Fourier Transform Infra-Red Spectrometry (FTIR), scanning electron microscopy (SEM), and Brunauer–Emmett–Teller) (BET) were used for the biochar characterization. Batch experiments were carried out in a laboratory to assess the adsorption of topramezone on soil through equilibrium and kinetic modeling under biochar addition. The clay content has been found to be higher under NT (18.24 ± 0.01) than under RT (15.91 ± 0.02). The total organic carbon was higher under NT. The topramezone adsorption equilibrium reached after 8 and 12 h, for NT and RT, respectively. The kinetic and thermodynamic analyses showed the adsorption under both treatments matched with pseudo-second-order kinetic and Langmuir models, respectively. After biochar addition, the pesticide adsorption capacity (40 < 25 < 15 °C) increased with decreasing temperature suggesting an exothermic adsorption process while negative values of Gibbs free energy (ΔG); −1848.07 and −366.531 J mol(−1); for the soil under NT and RT at 25 °C, respectively, indicated spontaneous adsorption. Negative entropy values (ΔS); −21.92 and −78.296 J mol(−1)K(−1), for NT and RT, respectively, explained a decreased randomness process. The enthalpy was higher (p < 0.05) under RT (−23,274.6 J mol(−1)) than under NT (−1313.73 J mol(−1)). Conclusively, it was shown that the topramezone adsorption capacity was higher under NT, and biochar addition increased more pesticide adsorption under NT than under RT.